Developing patterns of students' mathematical literacy processes: Insights from cognitive load theory and design-based research - Andes Safarandes Asmara; Stevanus Budi Waluya; Hardi Suyitno; Iwan Junaedi; Yusi Ardiyanti (IKIP Siliwangi and I-MES, 2024)
This research aims to develop patterns of students' mathematical literacy processes based on the Cognitive Load Theory (MLCLT). Research using Design-Based Research (DBR) aims to design and develop learning components in the form of resulting learning patterns arranged in 4 stages. The research results show that a CLT-based mathematical literacy process domain pattern has been found. For the aspect of formulating situations mathematically, the pattern of mathematization was produced, and it resulted in some students having good communication skills. For the element of employing mathematical concepts, facts, procedures, and reasoning, the pattern of application was produced, and it showed an increase in students' literacy processes for indicators such as mathematizing, representation, reasoning, argument, devising strategies for solving problems, using symbolic, formal, and technical language and operations, as well as using mathematical tools. The pattern for the aspect of interpreting, applying, and evaluating mathematical outcomes is the reflection pattern. In this pattern, students are already accustomed to having indicators of mathematical literacy processes related to devising strategies for solving problems, using symbolic, formal, and technical language and operations, as well as using mathematical tools so that they can produce real solutions to real-world problems.